PELATIHAN PEMBUATAN KERIPIK SINGKONG DAN PENERAPAN TEKNOLOGI KEMASAN PRODUK LOKAL DI KELURAHAN PALANGGA KECAMATAN DURUKA KABUPATEN MUNA - R Marsuki Iswandi; La Ode Muhammad Harjoni Kilowasid; yusriadin; Nurchalisah Rustan M; Edi Syah Mihrad (Jurnal Pengabdian Masyarakat Pinang Masak, 2026)
The purpose of this activity is to empower the community through training in cassava chip production and the application of modern packaging technology to increase the added value of local food products. The potential of cassava commodities in Palangga Village, Duruka District is very high, but its utilization is still limited to the sale of raw materials with low economic value. This condition is caused by the community's limited knowledge of hygienic processing, proper frying techniques, and packaging systems that can maintain product quality and shelf life. The community service activity was carried out using a participatory approach that involved farmer groups and housewives as key partners. All stages of the training were carried out through demonstrations and hands-on practice so that participants could understand and apply the skills they had acquired independently in their own households. The results of the activity showed a significant increase in the community's knowledge and skills in food processing and packaging technology. The products resulting from the training had a longer shelf life, stable crispness, and a more professional packaging appearance. Participants are able to operate simple packaging tools and develop creativity in product label design. The impact of the activity is immediately felt through the growth of entrepreneurial motivation among housewives and increased public interest in developing small businesses based on local agricultural products.